Lifecycle environmental benefits of integrated rational fertilization, biochar, and constructed wetland in mitigating nutrient loading - Yu-Ning Chen; Chihhao Fan; Michal Šereš; Markéta Šerešová; Jan Vymazal; Shu-Yuan Pan (Agricultural Water Management)
Agricultural activities due to fertilization contribute significantly to nutrient loadings and other environmental burdens, posing a severe threat to ecosystems. Although a portfolio of green agricultural practices is recommended, few studies address the environmental benefits from a life-cycle perspective. This study comprehensively evaluates the cradle-to-gate environmental benefits of integrating rational fertilization, biochar, and constructed wetlands (CWs) exemplified by plum cultivation. Four assessment scenarios were designed: (S1) conventional cultivation, (S2) rational fertilization with biochar amendment, (S3) conventional cultivation with a simulated CWs system, and (S4) rational fertilization with biochar amendment and a simulated CWs system. In the assessment, rational fertilization used half the fertilizer compared to conventional practices, biochar was applied at 0.1 ton/ha, and horizontal subsurface flow CWs were filled with washed gravel and planted with Phragmites australis. The findings show that rational fertilization combined with biochar (S2) or CWs (S3) alone show about half the eutrophication impacts of conventional cultivation (S1). Combining rational fertilization, biochar and CWs (S4) further reduces freshwater and marine eutrophication potentials by ∼73.5 % and ∼69.8 %, respectively. Similarly, these green agricultural practices (either S2 or S4) effectively reduce the overall endpoint impacts by about 47 %, with synergistic improvements, particularly in endpoint freshwater ecotoxicity and freshwater eutrophication, observed for S4 (a significant reduction of 76 %) compared to S1. Regarding the carbon footprint, the production of plums using conventional agriculture emits ∼300 kg CO2-eq per ton-plum, whereas using green agricultural practices results in only ∼138 kg CO2-eq per ton-plum, representing a reduction of 45.8 % in greenhouse gas emissions. This study highlights the potential of green agricultural practices to mitigate NPS nutrient loadings to aquifers and achieve sustainable agricultural management through reduced global warming and other environmental impacts.